2018
DOI: 10.1038/s41380-018-0297-9
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and its impact on adolescent brain development and psychopathology

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 67 publications
3
58
2
1
Order By: Relevance
“…For example, peer victimization has been shown to be a contributor to mental health disorders 46,47 , even above and beyond that of family background and genetic risk 48 , but if and how the brain moderates these relationships was unknown. In IMAGEN we showed for the first time that peer victimization results in increased generalized anxiety in part by affecting the rate of structural brain development across adolescence 49 . Early interventions to reduce these exposures could mitigate the changes in brain structure underlying the development of mental disorders.…”
Section: Environmental Impact On Neural Mechanisms Of Mental Disordersmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, peer victimization has been shown to be a contributor to mental health disorders 46,47 , even above and beyond that of family background and genetic risk 48 , but if and how the brain moderates these relationships was unknown. In IMAGEN we showed for the first time that peer victimization results in increased generalized anxiety in part by affecting the rate of structural brain development across adolescence 49 . Early interventions to reduce these exposures could mitigate the changes in brain structure underlying the development of mental disorders.…”
Section: Environmental Impact On Neural Mechanisms Of Mental Disordersmentioning
confidence: 93%
“…In addition to identifying psychopathology predictors we aim to establish longitudinal trajectories of neurobehavioral development during adolescence and young adulthood that relates to reinforcement-related psychopathology. In a recent study we identified a groups of adolescents who were chronically victimized by their peers across adolescence 49 . By age 19 these individuals had higher rates of anxiety, depression, and hyperactivity.…”
Section: Using Longitudinal Data To Develop Prediction and Developmenmentioning
confidence: 99%
“…Because childhood victimization may affect brain development, and negative life events are associated with lasting changes in neuroticism, we hypothesized that childhood victimization may affect neuroticism via changes in brain development, and then neuroticism may act as a mediating factor between childhood victimization and depression in adulthood. 13,14 In this case-control study, we conducted a self-administered questionnaire-based investigation, assessing depressive symptoms, neuroticism, and the degree and frequency of victimization. This study used path analysis to investigate the effects of the experience of being victimized in childhood on depressive symptoms in healthy controls and patients with major depressive disorder (MDD), and the distinction between controls and MDD in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation involving more accurate data collection on this transaction between the school system and the parental system would definitely be helpful in the development of both intervention and prevention programs, as well as, further exploration of the protective and risk factors within each system that may influence the prevalence of bullying within educational settings. Those adolescents who have witnessed scenes of aggression at home frequently constitute a group at risk and recent brain-image studies show the impact of chronic peer-victimization at a neurological level for the adolescent's brain development (Quinlan et al, 2018). The characteristics of this population should be studied more depth in order to provide teachers, schools and other professionals with accurate and effective early detection and evidence-based intervention to deal and mitigate the harm that bullying can have as a traumatic experience in the school context and beyond.…”
Section: Discussionmentioning
confidence: 99%